Design Build Dryer Machine Frying Results Nuts Eggs - Purwantono, Purwantono; Waskito, Waskito; Rinaldo, Putu Satria; primawati, primawati (Universitas Negeri Padang, 2018)
The purpose of this research is to design oil drying machine in nurts eggs to get the result of working drawing and to determine the peanut dryer component. The concept of planning oil drying machine in nurts eggss is by conducting a direct survey of the egg industry, the problems arise still high levels of oil in manually dried peanuts, then carry out the design concept. Based on the concept, then designed a design drawing. The result of this final task is in the form of design or design of oil oven dryers that utilize centrifugal force for drying oil, oil stainless steel rotary tube components, stainless steel container tube with stainless steel , axle components to support tubes of 22mm diameter and 520mm length, pulleys with a 3/6 ratio as a rotary reducer of an electric motor of 0.5 HP 1400 rpm to 500 rpm. Frame profile machine L 40 x 40 x 4 mm 42 st material and engine components made by Fernando Ferry from material st 37.